A arte rupestre de Jequitaí entre práticas gráficas "'padronizadas'" e suas manifestações locais : interseções estilísticas no sertão mineiro - Rogério Tobias Junior (2010)
This work focuses the rock art of seven pre-historic rock shelters located at the mid-lower course of the Jequitaí river, north of the state of Minas Gerais. It privileges a stylistic analysis of the graphic complexes towards the construction of a micro regional cronostylistic table and the comparison with neighbor regions. The classification method here adopted aims to integrate different variables of the graphic complexes observed and the landscape in which they are included, amplifying the possibilities of stylistic association beyond the limits imposed by the simple formal analysis of the drawings, and incorporating effective possibilities in the identification of the choice patterns involved in the act of drawing. It is of fundamental relevance the discussion around the concept of landscape and the establishment of a coherent comprehension of the relations between human beings and that specific landscape of Jequitaí. This approach was chosen due to the existence of previous hypotheses about Jequitaí’s rock art that allege the existence of a “transitional character” at the graphic complexes there observed, determined by distinct environmental factors acting at the same places: the presence of different lithologies, that has led to the region’s characterization as a place of geoestructural transition, of the superposition of different phytophysionomies (cerradão e caatinga) and different climatic influences. This work´s conclusion goes toward one of the possible interpretations to the rock art´s graphic variability and choice patterns involved, based on the possibility of exchange of different repertories, identifiable at this research´s region of interest. More than a transition, a Stylistic Intersection was really observed between the Stylistic Units, as described regionally by other archaeologists, developing locally singular behaviors when compared to their other regions correspondents, mainly the rock art attributed to the São Francisco and Planalto Tradition.